Developing anaerobic power and capacity for combat sports athletes - João Paulo Lopes-Silva (Universidad de León, 2021)
This chapter describes the physiological responses associated with anaerobic power and capacity of combat sports athletes from different modalities (judo, Brazilian jiu-jitsu, wrestling, Olympic boxing, karate, and Muay Thai) during specific situations. Next, the most used evaluation methods for the control and monitoring of these variables are presented. Finally, based on longitudinal studies that evaluated the effects of anaerobic power and capacity training of combat sports athletes, the main training approaches are presented.